2023
DOI: 10.31083/j.fbl2806127
|View full text |Cite
|
Sign up to set email alerts
|

Proline cis/trans Isomerization in Intrinsically Disordered Proteins and Peptides

Fanni Sebák,
János Szolomájer,
Nándor Papp
et al.

Abstract: Background: Intrinsically disordered proteins and protein regions (IDPs/IDRs) are important in diverse biological processes. Lacking a stable secondary structure, they display an ensemble of conformations. One factor contributing to this conformational heterogeneity is the proline cis/trans isomerization. The knowledge and value of a given cis/trans proline ratio are paramount, as the different conformational states can be responsible for different biological functions. Nuclear Magnetic Resonance (NMR) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the trans configuration, proline has ω = 180°, while in cis , ω = 0°. A transition of cis to a syn (ω = 90°) state needs to overcome a ∼30 kcal mol –1 energy barrier, leading to a predominantly trans conformation. , Experimental measurements consistently demonstrate slow cis-to-trans conversion rates. Phosphorylation affects cis–trans isomerization rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the trans configuration, proline has ω = 180°, while in cis , ω = 0°. A transition of cis to a syn (ω = 90°) state needs to overcome a ∼30 kcal mol –1 energy barrier, leading to a predominantly trans conformation. , Experimental measurements consistently demonstrate slow cis-to-trans conversion rates. Phosphorylation affects cis–trans isomerization rates.…”
Section: Discussionmentioning
confidence: 99%
“…After looking at many sequences of functional tau fragments, they did not find high number of cis conformation in Thr231–Pro232 segment (Ahuja et al, 2016). Recently, an NMR study showed that at least in some IDPs, ratio of cis / trans conformations of Pro depends upon occurrence of aromatic and charged side chains in the neighboring sequences (Sebak et al, 2023). Also, Mateos et al (2020) studied an IDP osteopontin by NMR and found Pro having a role in nucleation of its central compact region.…”
Section: Some Amino Acids Enable Intrinsic Disorder In Proteinsmentioning
confidence: 99%